KECUKUPAN KETAHANAN PANGAN DESA DENGAN MENERAPKAN FUNGSI-FUNGSI MANAJEMEN DI DESA TIMBUSENG KECAMATAN POLONGBANGKENG UTARA KABUPATEN TAKALAR - Nur Naninsih; Abdul Syukur; Dewi Pratiwi Indriasari; Nur Fatma (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
The Timbuseng village government always socializes the importance of food security by providing training, besides that the village government also prepares the village budget according to the needs of the community and its implementation has been measured because all activities are carried out properly. The community participates in every village program, thus the community is aware and motivates one another. So that the activities that have been carried out continue to run well, the government and partners always coordinate.